PROTOTYPE KNOWLEDGE MANAGEMENT SYSTEM RESPONSIVE MOBILE ANDROID UNTUK INOVASI UKM KOTA DEPOK DENGAN METODE MOST ADMIRED KNOWLEDGE ENTERPRISE (MAKE) - Sunarti Sunarti; Yunita Yunita (LPPM Universitas Bina Sarana Informatika, 2016)
Abstract - Small and Medium Enterprises (UKM) have an important role in economic growth. One important factor that will increase the products of UKM is information technology. Information technology can be seen as a tool or medium to acquire knowledge and information as well as a tool in running the business process. Intellectual capital and knowledge management are closely linked with the development of information technologies that drive the globalization era. The term knowledge management first appeared in the business world. Preliminary studies on knowledge management has been conducted in the mid-1980s partly by Sveiby and Iloyd. As said by Fatwan (2006), factors affecting the business environment today is no longer the era of information, but it has been switched to the era of knowledge. Knowledge Management System (KMS) inspired the growth of culture for knowledge sharing (shared knowledge). Benefits of Knowledge Management System that is creating, documenting, classifying and disseminating knowledge in the organization. The UKM applying the concept of Knowledge Management System with Mobile responsive Android in the promotion of UKM, UKM cooperation, exhibitions, trade missions, data and information empowerment of UKM that are processing and the development of market access for UKM. Through this research can know the extent of the Prototype application of the knowledge management system responsive Mobile Android in hopes of getting additional information and knowledge in developing a business that could affect the level of investment UKM.Keywords: Knowledge Management System, Mobile Android, UKMAbstrak - Usaha Kecil dan Menengah (UKM) mempunyai peranan yang penting dalam pertumbuhan ekonomi. Salah satu faktor penting yang akan meningkatkan produk UKM adalah teknologi informasi. Teknologi informasi tersebut bisa dipandang sebagai alat atau media untuk memperoleh pengetahuan dan informasi serta sebagai alat dalam menjalankan proses bisnis. Modal intelektual dan manajemen pengetahuan sangat erat kaitannya dengan perkembangan teknologi informasi yang mendorong era globalisasi. Istilah knowledge management pertama kali muncul di dunia bisnis. Studi awal tentang knowledge management telah dilakukan pada pertengahan tahun 1980-an antara lain oleh Sveiby dan Iloyd. Seperti yang dikatakan oleh Fatwan(2006), faktor yang mempengaruhi lingkungan bisnis saat ini bukan lagi era informasi, tetapi sudah beralih ke era pengetahuan. Knowledge Management System (KMS) menginspirasi tumbuh kembangnya budaya saling berbagi pengetahuan (share knowledge). Manfaat Knowledge Management System yaitu menciptakan, mendokumentasikan, menggolongkan dan menyebarkan knowledge dalam organisasi. Para UKM menerapkan konsep Knowledge Management System dengan responsive Mobile Android dalam promosi produk UKM, kerjasama usaha UKM, pameran, misi dagang, data dan informasi pemberdayaan UKM yang bersifat pemrosesan dan pengembangan akses pasar bagi produk UKM. Melalui penelitian ini dapat diketahui sejauh mana Prototype penerapan knowledge management system responsive Mobile Android dengan harapan mendapatkan tambahan informasi dan pengetahuan dalam mengembangkan usahanya yang bisa mempengaruhi tingkat investasi UKM.Kata Kunci: Knowledge Management System, Mobile Android, UKM